To convert the equation y = 1/6x + 4 into standard form, we need to eliminate any fractions and rewrite the equation using integers. Here's the step-by-step process:
1. Multiply both sides of the equation by 6 to eliminate the fraction:
6 * y = 6 * (1/6x + 4)
Simplifying the right side:
6y = x + 24
2. Rearrange the equation to isolate x and y terms:
x + 24 = 6y
Subtracting x from both sides:
24 = 6y - x
3. To have the variables in standard form, we typically prefer to have the coefficient of x positive. Multiply both sides by -1:
-1 * 24 = -1 * (6y - x)
Simplifying the right side:
-24 = -6y + x
4. Now the equation is in standard form, but to comply with the requirement of using integers, we need to rearrange it further:
-6y + x = -24
Therefore, the equation y = 1/6x + 4 in standard form using integers is:
-6y + x = -24
Write y= 1/6x + 4 in standard form using integers. Show your work.
Responses
-x-6y=24
-x+6y=24
-x+6y=4
6x-y=24
1 answer